2020
DOI: 10.4103/jfmpc.jfmpc_5_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the relationship between information literacy and evidence-based nursing and their impact on knowledge and attitude of nurses working in hospitals affiliated to Kerman University of Medical Sciences on medication errors

Abstract: Introduction and Purpose: Nowadays, due to the importance of information literacy in obtaining documented and credible information, the necessity of nurses to achieve high levels of information literacy to improve their performance in accessing documentary and scientific information has become more evident. Objective: The aim of this study was to investigate information literacy, evidence-based nursing, nurses 'attitudes, nurses' knowledge, medication errors, Kerman Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…This is similar to the results of significantly increased problem-solving ability and evidence-based nursing ability when providing the nursing information capacity enhancement program to 72 nursing students in the study by Ha et al [19]. In addition, a study of clinical nurses [22] depicts a similar result, as shown in our results, that information literacy has a positive effect on problem-solving ability.…”
Section: The Relationship Among the Acceptance Intention Of A Smart Device Information Literacy And Problem-solving Confidencesupporting
confidence: 91%
See 1 more Smart Citation
“…This is similar to the results of significantly increased problem-solving ability and evidence-based nursing ability when providing the nursing information capacity enhancement program to 72 nursing students in the study by Ha et al [19]. In addition, a study of clinical nurses [22] depicts a similar result, as shown in our results, that information literacy has a positive effect on problem-solving ability.…”
Section: The Relationship Among the Acceptance Intention Of A Smart Device Information Literacy And Problem-solving Confidencesupporting
confidence: 91%
“…Information literacy is related to the problem-solving abilities of nurses [19,20]. In addition, the results of a study on nursing students demonstrated that information literacy affects evidence-based performance skills [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The value for this test was 1.640. The value for the Durbin Watson test need to be greater than 1.5 and less than 2.5 to fulfill this assumption (25). The results of the multiple linear regression showed that the R square value was 0.378 while that of the R square adjusted was 0.327.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing managers, especially top nursing managers, are a statistically significant force in the success of EBP because they understand the importance of evidence‐based interventions and policies, have the potential to change healthcare system, and allocate human and material resources to nurses' work environment (Azami et al, 2020; Farokhzadian et al, 2016). Hence, it is necessary to investigate nursing managers' perspectives on EBP and how to implement it.…”
Section: Introductionmentioning
confidence: 99%
“…
Evidence-based practice (EBP) is a decision-making method that has become an important component of health care in recent decades (Adib-Hajbaghery, 2006) and is recognized as a way to improve healthcare standards and excellence in nursing care (Azami et al, 2020). As a problem-solving method, EBP integrates the best available scientific evidence with clinical expertise, situational conditions, available resources and patient preferences (Renolen et al, 2018).
…”
mentioning
confidence: 99%